Methodology and Evaluation of Contemporary Islamic Learning: Between Tradition, Innovation, and Contextualization - Nur Azizah; Pipin Marti; Suparmita Suparti (JISEI: Journal of Islamic Studies and Educational Innovation, 2026)
Times, technological advances and changing societal needs require Islamic education to continue to adapt through the development of learning methodologies and evaluations that are relevant to the contemporary context. Islamic education not only functions as a means of transferring knowledge, but also as a medium for forming students' character, spirituality and social abilities. This research aims to analyze the methodology and evaluation of contemporary Islamic learning from the perspectives of tradition, innovation and educational contextualization. The research method used is a literature study with a descriptive-analytical approach through the study of various scientific literature, books and Islamic education journals. The research results show that contemporary Islamic learning methodology is experiencing a transformation from traditional approaches to more participatory and contextual learning, such as student centered learning, problem based learning, and the use of digital technology. On the other hand, learning evaluation is also developing through the application of authentic assessments, competency-based evaluations, as well as Islamic character assessments which cover cognitive, affective and psychomotor aspects in a balanced manner. Contextualization of learning is important so that Islamic values ​​remain relevant to the challenges of globalization without abandoning sharia principles. Thus, methodological innovation and evaluation are important strategies in improving the quality of Islamic education that is adaptive, humanistic and oriented towards the formation of human beings.